2009
DOI: 10.1152/ajprenal.90248.2008
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the epithelial sodium channel by membrane trafficking

Abstract: Butterworth MB, Edinger RS, Frizzell RA, Johnson JP. Regulation of the epithelial sodium channel by membrane trafficking.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
106
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 113 publications
(109 citation statements)
references
References 206 publications
(217 reference statements)
3
106
0
Order By: Relevance
“…[3][4][5][6][7] Because of its role in the regulation of Na + homeostasis, ENaC has been associated with clinical defects of Na + and water transport. 8 In the kidney, ENaC is localized in principal cells of the distal nephron (distal convoluted tubule and collecting duct), where it participates in final Na + uptake from the luminal urinary space.…”
mentioning
confidence: 99%
“…[3][4][5][6][7] Because of its role in the regulation of Na + homeostasis, ENaC has been associated with clinical defects of Na + and water transport. 8 In the kidney, ENaC is localized in principal cells of the distal nephron (distal convoluted tubule and collecting duct), where it participates in final Na + uptake from the luminal urinary space.…”
mentioning
confidence: 99%
“…Multiple mechanisms are known to participate in the regulation of ENaC activity, including limited proteolysis (30,43,44), hormonal mediated effects on translocation and membrane assembly (9,13,45,46), a serum and glucocorticoid-regulated kinase (SGK-1)-mediated phosphorylation of Nedd4 -2 leading to reduced ubiquitination, retrieval and degradation (17,18,47,48), as well as negative and positive hormonal effects mediated by protein kinases including ERK1/2, protein kinases A and C, and phosphatidylinositol 3-kinase, among others (14 -19, 47-49). Added to the above is the present identification of the Cyp2c44 epoxygenase and its EET metabolites as a new class of in vivo regulators of ENaC activity.…”
Section: Discussionmentioning
confidence: 99%
“…The route of transport of the subunits apparently proceeds via the Golgi complex and the trans-Golgi network. The proteins are then probably packaged in vesicular endosomes that are directed to the apical membrane (5,36). Studies on a variety of apical proteins have revealed several alternative routes of vesicular trafficking (41).…”
Section: Discussionmentioning
confidence: 99%
“…Studies on a variety of apical proteins have revealed several alternative routes of vesicular trafficking (41). In some cell types, ENaC appear to be transported in membrane lipid raft domains (5).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation